2003
DOI: 10.1080/0277221042000
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls, polycyclic aromatic hydrocarbons and alkylphenols in sediments from the Odra River and its tributaries, Poland

Abstract: Concentrations of polychlorinated biphenyls (PCBs), polycyclic aromatic hydrocarbons (PAHs), nonylphenol (NP) and octylphenol (OP) were measured in sediments collected during June-August 1998 along the Odra River and its tributaries (Warta, Obrzyca, Barycz, Kaczawa and Bo´br Rivers) in Poland. In addition, raw and treated sewage sludge collected from Gdan´sk, Poland, were analyzed for the target compounds. Concentrations of PCBs in sediments varied widely, ranging from 2.7 to 412 ng/g, on a dry weight basis (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Kannan et al (2003) detected significant amounts of nonylphenol (6670 -154 000 ng g -1 d.w.) and 4-tert-octylphenol (361 -4320 ng g -1 d.w.) in the sludge from the Gdansk Wschód wastewater treatment plant. Moreover, the same authors found considerable amounts of nonylphenol and 4-tert-octylphenol in sediments collected from the Odra River; the respective mean and maximum concentrations were 232 and 757 ng g -1 d.w. for nonylphenol (Szczecin), and 2.89 and 9.8 ng g -1 d.w. for 4-tert-octylphenol.…”
Section: Introductionmentioning
confidence: 99%
“…Kannan et al (2003) detected significant amounts of nonylphenol (6670 -154 000 ng g -1 d.w.) and 4-tert-octylphenol (361 -4320 ng g -1 d.w.) in the sludge from the Gdansk Wschód wastewater treatment plant. Moreover, the same authors found considerable amounts of nonylphenol and 4-tert-octylphenol in sediments collected from the Odra River; the respective mean and maximum concentrations were 232 and 757 ng g -1 d.w. for nonylphenol (Szczecin), and 2.89 and 9.8 ng g -1 d.w. for 4-tert-octylphenol.…”
Section: Introductionmentioning
confidence: 99%
“…analysed 7 indicator PCBs in marine sediments (2004) reported PCB levels ranging from 2.6 to 255 ng·g -1 dw in sediments from Ontario Lake in Canada. Kannan et al (2003) revealed PCB levels ranging from 2.7 to 412 ng·g -1 dw in sediments from Odra River and its tributaries in Poland.…”
mentioning
confidence: 99%
“…Here, also OCDD congener is among the most significant values. Another research in sediments collected from Odra river was conducted by Kannan et al [38]. Concentrations of PCBs in sediments ranged from 2.7 to 412 ng/g.…”
Section: Location and Description Of The Studied Ecosystemsmentioning
confidence: 99%